Effects of nephrectomy and KCl on transmembrane potentials, intracellular electrolytes, and cell pH of rat muscle and liver in vivo - Williams, J. A. (1971)
1. The ability of 24 hr nephrectomy and KCl to raise plasma K(+) concentration was used to correlate transmembrane resting potential (RP), ionic gradients, and cell pH (DMO method) in rat muscle and liver in vitro. 2. Effects of 24 hr nephrectomy on electrolytes included a rise in plasma K(+) and fall in Na(+), with a rise in intracellular K(+) and fall in intracellular Na(+) in both liver and muscle. Intracellular Cl(-) concentration rose in muscle and decreased in liver. 3. Measured muscle RP was decreased from -91 to -77 mV by 24 hr nephrectomy, with the RP predictable from the Goldman equation for Na(+) and K(+) with P(Na)/P(K) = 0·01 and Cl(-) behaving as if passively distributed. 4. Measured hepatic RP was increased from -43 to -48 mV by 24 hr nephrectomy, with a change in ionic permeability or activation of an electrogenic pump necessary to explain the results. 5. Plasma acid—base changes consisted of metabolic acidosis with partial respiratory compensation. Cell pH rose slightly in both liver and muscle; the H(+) gradient remained constant in muscle but increased slightly in liver. 6. KCl was injected into intact rats while the RPs were continuously measured in muscle or liver. Muscle RP was found to decrease and hepatic RP to increase along a similar time course. 7. Infusion of KCl into the portal vein led to an increase in the hepatic RP for values of hepatic venous K(+) of 15-25 mM, whereas infusion sufficient to increase the hepatic venous K(+) concentration to 30-40 mM produced no change or a slight decrease in hepatic RP. 8. The rat muscle RP can be adequately described by the Goldman equation for Na(+) and K(+), whereas the hepatic RP may well have both diffusion and electrogenic components which respond differently to an increase in plasma K(+) concentration.